Navigating Wartime Realities: Adaptation and Resilience in Ukrainian Social Work Education - Semigina, Tetyana; Stoliaryk, Olha (Socialinė teorija, empirija, politika ir praktika, 2025)
This paper explores how Ukraine’s Higher Education Institutions (HEIs) in social work have demonstrated resilience amidst the ongoing armed conflict. The war has significantly impacted the educational landscape, posing challenges to institutional operations, teaching methodologies, and the preparation of future social workers. The objective of this study is to explore the key factors contributing to both organizational and academic adaptability, thus ensuring that social work education remains relevant and effective in addressing the evolving needs of a wartime society.A mixed-methods approach was employed, combining a desk review with 12 semi-structured interviews with academic staff from departments and institutes offering programs in ‘Social Work’ and ‘Social Pedagogy’. The study examines how universities have adapted their curricula, teaching strategies, and assessment methods, while also highlighting the role of international cooperation and community-based initiatives.The results reveal that Ukrainian HEIs have demonstrated significant resilience, utilizing cognitive and behavioral strategies to adapt to the war’s challenges. This includes the shift to online and hybrid learning, the use of makeshift classrooms, and the integration of new community-focused missions. Despite these adaptive efforts, the findings also highlight concerns about the long-term sustainability of these changes, particularly in maintaining educational quality and meeting the needs of vulnerable populations. International partnerships have been crucial in supporting these efforts, although disparities between institutions in accessing such resources remain.This study underscores the importance of resilience in educational systems during crises and offers valuable insights for other higher education institutions facing similar challenges. It calls for a holistic approach to education, one that balances immediate adaptations with long-term strategic planning so that to ensure the continued relevance and quality of social work education in times of conflict.